PRÁTICAS DE MANEJO DE ERVA-QUENTE (Spermacoce latifolia Aubl.) NA REGIÃO CENTRO-SUL DO PARANÁ. - Santos, José Alfredo Baptista dos (2008)
With the objective of evaluating alternatives for oval-leaf false button weed management in black beans crops for familiar farmers of the Southern region of Paraná State, studies were carried out, in Ponta Grossa at Iapar Experimental Station and in Irati at a farmer field. A survey was also carried out to evaluated the management practices of oval-leaf false buttonweed by the farmers. One study in Ponta Grossa had as objective to evaluate the period of emergence of oval-leaf false buttonweed during one year, in area with and without vegetal covering, and also with and without mobilization of the soil. In another study also in Ponta Grossa an experiment was installed to evaluate the influence of cover crops in the reduction of the infestation of buttonweed in no-till with three winter cover crops: black oat, radish, black oat with common vetch and a fallow treatment. The experiment in the region of Irati had as objective to evaluate, besides the influences of cover crops, also the liming in the reduction of the population of buttonweed in black beans crop. The cover crops were the same as the experiment in Ponta Grossa. The management practices was evaluated through a questionnaire applied to seventeen farmers separated in two groups: 1) those who still regarded false buttonweed as a problem in the farm, and 2) those farmers who had false buttonweed as a problem but were able to solve it. In the study of period of emergence of false buttonweed the main peaks of flush were in October, November and December. The experiments to evaluate the effect of winter cover crops in Ponta Grossa and Irati have shown no effect on false buttonweed populations overall. There was also not diference in the liming treatments in Irati. The survey with the farmers of the region has shown that successfull farmers in the management of false buttonweed were those who use integrated weed management strategies.